Microbial determination of the mutagenicity of crude oil and decoctions from Jatropha Curcas Linn. (Physic nut) - Lumbay, Orcheliza M. (2002)
Microbial determination of the mutagenicity of crude seed oil and decoctions from Jatropha curcas leaves and bark was done using Ames Test. Two strains of Salmonella typhimurium were used, TA98 and TA102. Two separate set-ups with or without liver enzymes were made and three plates were prepared for each test material: (1) for spontaneous revertants (bacteria only), (2) for sterility test (test material only), and (3) treatment (bacteria + test material). The decoctions were incorporated in the minimal medium with top agar, bacterial strain and with or without liver enzymes. For the crude oil, a filter disc dipped in the extract was placed at the center of the plate. The crude oil induced no revertants possibly because it has antibacterial property. The average number of revertants was generally lower in treatments with liver enzymes than in those without liver enzymes. This was attributed to the use of old cultures in the activation step with liver enzymes. Therefore, whether the plant decoctions were pro-mutagens or not could not be established in this study. However, since the leaf and bark decoctions did not double the number of spontaneous revertants, they cannot be directly considered as mutagents under the experimental conditions employed
Thesis (BS Biology) -- University of the Philippines Mindanao, 2002